How does cultural capital influence academic achievement in the Chinese context? A systematic literature review - Fenlian Xie; Fonny Dameaty Hutagalung (SAGE Open)
This article reviewed how cultural capital theory is applied in China, focusing on the definition of cultural capital, the aspects of cultural capital most relevant to academic achievement, and the association between cultural capital and academic achievement. The review encompassed empirical studies published between 2001 and 2024, sourced from both English and Chinese databases, including Web of Science, Scopus, ERIC, and ProQuest, CNKI, Weipu , and Wanfang . A total of 20 quantitative and qualitative studies were included. Based on a convergent segregated approach, the article suggests that cultural capital in the Chinese context is defined as a cultural resource consisting of skills, knowledge, and dispositions that are acknowledged and rewarded in schools. In contrast to the focus on highbrow culture in Western research, parent-child reading, participation in shadow education, and English proficiency are emphasized as core aspects of cultural capital in the Chinese context. Additionally, the article finds a weaker association between cultural capital and academic achievement in China. These findings provide new insights into social reproduction in China, extending Bourdieu’s cultural capital theory, which suggests that unequal competition between classes exists within the family, to competition outside the family, such as shadow education and the acquisition of English language skills. Finally, this article discussed the applicability of lower-class cultural capital and provided directions for future research.